2009
DOI: 10.1073/pnas.0903304106
|View full text |Cite
|
Sign up to set email alerts
|

ANO2 is the cilial calcium-activated chloride channel that may mediate olfactory amplification

Abstract: For vertebrate olfactory signal transduction, a calcium-activated chloride conductance serves as a major amplification step. However, the molecular identity of the olfactory calcium-activated chloride channel (CaCC) is unknown. Here we report a proteomic screen for cilial membrane proteins of mouse olfactory sensory neurons (OSNs) that identified all the known olfactory transduction components as well as Anoctamin 2 (ANO2). Ano2 transcripts were expressed specifically in OSNs in the olfactory epithelium, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
377
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(426 citation statements)
references
References 37 publications
33
377
1
Order By: Relevance
“…Our N-terminal antibody did not detect a truncated protein in Ano2 -/-tissue, suggesting the occurrence of nonsensemediated mRNA decay, instability of the truncated protein, or both. Ano2 -/-mice were born at Mendelian ratio; they grew, mated, and survived normally and lacked an immediately apparent phenotype.Consistent with previous data [21][22][23] , western blots indicated that Ano2 is most highly expressed in olfactory epithelium (MOE and VNO) and eye tissue (Fig. 1a,b).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…Our N-terminal antibody did not detect a truncated protein in Ano2 -/-tissue, suggesting the occurrence of nonsensemediated mRNA decay, instability of the truncated protein, or both. Ano2 -/-mice were born at Mendelian ratio; they grew, mated, and survived normally and lacked an immediately apparent phenotype.Consistent with previous data [21][22][23] , western blots indicated that Ano2 is most highly expressed in olfactory epithelium (MOE and VNO) and eye tissue (Fig. 1a,b).…”
supporting
confidence: 92%
“…5d,f), but not at 13 µM free Ca 2+ (Fig. 5g,i) similar to data reported for Ca 2+ -activated Cl -currents for heterologously expressed Ano1 and Ano2 [20][21][22]33,34 and for frog OSNs 7 . We could not detect these Cl -currents in Ano2 -/-OSNs (Fig.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…2008) and ANO2 (TMEM16B) (Stephan et al . 2009; Stohr et al . 2009) subunits identified as bona fide CaCCs (see Pedemonte & Galietta, 2014 for review).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ANO2 has been identified as a CaCC subunit in the cilia of olfactory sensory neurons (Stephan et al . 2009; Billig et al . 2011).…”
Section: Introductionmentioning
confidence: 99%